LncRNA UCA1 maintains the low‐tumorigenic and nonmetastatic status by stabilizing E‐cadherin in primary prostate cancer cells. Issue 10 (17th August 2020) - Zhao, Xian; Wang, Yanli; He, Jianfeng; Deng, Rong; Huang, Xiaojun; Guo, Yanmin; Li, Lian; Xie, Ruiyu; Yu, Jianxiu
Abstract: Long noncoding RNAs (LncRNAs) have emerged as important players in cancer biology. Increasing evidence suggests that LncRNAs are frequently dysregulated in cancer and may function as oncogenes or tumor suppressors. Urothelial carcinoma associated 1 (UCA1), a LncRNA, firstly identified in bladder transitional cell carcinoma, seems to act as an oncogene in many different types of human cancers by promoting cell proliferation and migration. In this study, we revealed a novel biological function of UCA1, which was different from that reported by previous studies, was responsible for maintaining the low‐tumorigenic, nonmetastatic phenotypes in primary prostate epithelial cells. UCA1 could stabilize E‐cadherin protein by preventing the interaction between E‐cadherin and its E3 ligase MDM2, which suppressed MDM2‐mediated ubiquitination and degradation of E‐cadherin. In addition, we also found that UCA1 acted as a sponge of miR‐296‐3p, which targeted E‐cadherin gene CDH1 messenger RNA at the posttranscription level. Taken together, these findings demonstrated that UCA1 had a new important role in effectively keeping E‐cadherin at a high level through a dual mechanism, which maintained primary prostate cancer cells at the low‐tumorigenic and nonmetastatic status.